Tinjauan Yuridis Putusan Hakim Mengenai Perbuatan Melawan Hukum dalam Sangketa Pertanahan Pada Putusan Kasasi Mahkamah Agung Nomor 4655 K/PDT/2023 - Andryawan Andryawan; Yoel Calvianson; Fryana Satriani; Nathania Apriza; Dhiny Ellen Juwita; Talitha Inas Tsabitah (Dinasti Research, 2025)
The Supreme Court's decision in Case No. 4655 K/Pdt/2023, which involves a land ownership dispute between PT Sarana Subur Agrindotama and H. Muhammad Noor alias Amat Iras, serves as an important reference in the development of agrarian law, particularly regarding the ownership of Right to Cultivate (HGU) certificates in Indonesia. This dispute addresses unlawful conduct in the form of land control that is inconsistent with applicable legal principles, specifically regulated in Article 1365 of the Indonesian Civil Code (KUHPer). Through an analysis of legal considerations and presented evidence, the Supreme Court decisively ruled on the rights and ownership boundaries involving HGU and individual rights to land. This article explores the implications of this decision, including its impact on legal protection for HGU holders and community rights to land, and examines the decision's influence on future land management in Indonesia.